(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2016)
Semi-preparative High Liquid Column Chromatographic separation of the ethyl acetate soluble fraction of a methanol extract of the leaves of Loranthus micranthus Linn. parasitic on Hevea brasiliensis (Willd. ex A. Juss.) led to the isolation of two gallic acid derivatives (1-2). The structures of the compounds were solved by using spectroscopic methods (1D and 2D NMR and mass spectroscopic data) as well as by comparison with literature values. The compounds were identified as 3,4,5-tri-O-methyl gallic acid (1) and methyl 3-O-methyl gallate (2). The antioxidant activity of the isolated compounds was evaluated by using DPPH assay. Compounds 1 and 2 showed strong antioxidative capacity with inhibitory concentration (IC50) values of 10.0 ± 0.03 and 45.0 ± 0.02 ?M, respectively. Dhaka Univ. J. Pharm. Sci. 14(2): 139-145, 2015 (December)